1978
DOI: 10.1080/00222216.1978.11969367
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of the Deer Hunting Experience: A Cluster-Analytic Study

Abstract: Using data from Washington State deer hunters, this paper reports on a cluster analytic study of the attributes of the deer hunting experience. The data were collected by mail ques tionnaire from 3,924 deer hunters by Potter, Hendee, and Clark (1973). Scaled data were subjected to a variable cluster analysis, and then variable clusters were used in an object cluster analysis of hunters. Several dimensions of the deer hunting experience which add to or detract from satisfaction, and groups of hunters reacting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…Stability of Facture Structure of Leisure Meanings 53 motivational (e.g., Atkinson, 1957) psychology, and have noted the usefulness of such information in devising and selecting management objectives, organizing and conducting recreation inventories, selecting management practices, valuing the experience and the resource, and developing visitor information programs (Knopf et al, 1973;Driver, 1975;Driver and Brown, 1975;Brown et al, 1977;Brown and Haas, 1978;Brown et al, 1978;Driver and Brown, 1978;Driver and Cooksey, 1978;Hautaluoma and Brown, 1978).…”
mentioning
confidence: 97%
“…Stability of Facture Structure of Leisure Meanings 53 motivational (e.g., Atkinson, 1957) psychology, and have noted the usefulness of such information in devising and selecting management objectives, organizing and conducting recreation inventories, selecting management practices, valuing the experience and the resource, and developing visitor information programs (Knopf et al, 1973;Driver, 1975;Driver and Brown, 1975;Brown et al, 1977;Brown and Haas, 1978;Brown et al, 1978;Driver and Brown, 1978;Driver and Cooksey, 1978;Hautaluoma and Brown, 1978).…”
mentioning
confidence: 97%
“…The ROS.was designed as a regional, recreation planning tool to help planners and managers to conduct inventories, design target management standards, decide among alternative management actions, and provide a larger framework and context for multiple use recreation resource planning (Brown et al, 1978;Driver & Brown, 1978;Clark & Stankey, 1979a;Driver et aI., 1987). These developments in the ROS concept lead to the adoption of the ROS by the USFS and subsequent publication of the planning concept in U.S. Forest Service planning and management documents, such as the "ROS Users Guide."…”
Section: Introductionmentioning
confidence: 99%
“…That hunters seek a variety of harvest and nonharvest experiences and satisfactions from their activity is well documented (Hammitt, McDonald, & Patterson, 1990;Hautaluoma & Brown, 1978;Hazel, Langenau & Levine, 1990;Hendee, 1974;Potter, Hendee, & Clarke, 1973;Vaske, Fedler & Graefe, 1986). It has been argued that wildlife managers should recognize the broad range of experiences sought by hunters in managing for quality hunts (Decker, Brown & Gutierrez, 1980;Driver, 1985).…”
Section: Literature Reviewmentioning
confidence: 95%
“…Their results indicated that hunter types differ on social and management preferences such as number of hunters, access improvement, manner of information dissemination, and preferred types of hunting licenses and permits (e.g., either-sex permits). Hautaluoma and Brown (1978) identified 10 hunter types with cluster analysis "according to their patterns of satisfactions" (p. 276) scores. Several dimensions contributing to hunter satisfaction were identified, including nature enjoyment, harvest equipment, out-group contact, and skill development.…”
Section: Hunter Types and Setting Preferencesmentioning
confidence: 99%
See 1 more Smart Citation